Psychometric Properties of Diabetes Management Self-Efficacy in Thai Type 2 Diabetes Mellitus Patients: A Multicenter Study - Monthida Sangruangake; Chananya Jirapornkul; Cameron Hurst (International Journal of Endocrinology)
Objective. The aims of this study were to translate and psychometrically evaluate the Thai version of diabetes management self-efficacy scale (T-DMSES) and to examine its association with HbA1c control in diabetic individuals. Methods. This study recruited patients from outpatient diabetes clinics of both community and university hospitals. The first phases of this study involved translation of the existing DMSES into Thai, and in the second phase, we evaluated its psychometric properties. The construct validity was evaluated using confirmatory factor analysis. Criterion validity of DMSES was subsequently evaluated by examining DMSES’s association with HbA1c control. Results. The T-DMSES contains 20 items across four factors. Confirmatory factor analysis demonstrated the construct validity of T-DMSES (χ2=645.142, df = 164, p<0.001, CFI = 0.98, RMSEA = 0.065, TLI = 0.977, and AGFI = 0.981). The T-DMSES was also shown to be criterion valid with most subscales highly associated with HbA1c control. Conclusion. The T-DMSES was shown to have good psychometric properties. It is likely to provide valuable insights into the epidemiology of diabetes management self-efficacy and may also prove useful in evaluating interventions for raising diabetes management self-efficacy, which in turn, improve both patient self-management and blood sugar control.